Factors Affecting Audit Opinions in Companies Listed on the Indonesia Stock Exchange - Fitri Yani Jalil; Triana Meinarsih; Dian Widyantini; Andi Andi (Oikonomia : Journal of Management Economics and Accounting, 2025)
Audit opinion has an important role in economic decision making because it reflects the credibility of the company's financial statements. Internal factors, such as profitability, liquidity, ownership structure, and corporate governance, strongly influence the audit opinion given by the auditor. Companies with high profitability are likely to receive an unqualified audit opinion, while companies with low profitability risk getting a modified opinion. Good liquidity also increases the likelihood of a positive audit opinion. A concentrated ownership structure can reduce audit quality due to potential manipulation of financial statements, while dispersed ownership supports transparent governance. Regulations implemented by the OJK and IDX, as well as auditor independence, play an important role in improving audit opinion quality. Strict regulatory policies can strengthen the credibility of audit opinions, but pressure from company management can threaten auditor independence. Large audit firms, such as the Big Four, tend to provide more credible opinions, but strict internal controls are still needed. This research uses a qualitative approach with case studies on companies listed on the Indonesia Stock Exchange to analyze the factors that influence audit opinion. It is hoped that this research can provide insight into how to improve the transparency and credibility of audit opinions, as well as the role of regulators in strengthening the stability of the Indonesian capital market.